PENGARUH REKRUTMEN, KOMPETENSI KARYAWAN DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PT SUKSES MITRA SEJAHTERA - Wulansari, Femilia (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
This research is motivated by Improving employee performance will bring progress for companies to be able to survive in an unstable business environment competition. Researchers found several interesting things to be researched, such as recruitment that is not in accordance with SOPs, suboptimal competencies, less assertive leadership and less than-optimal employee performance at PT. Mitra Sejahtera Success. The purpose of this study is to determine the influence of recruitment, employee competence, and leadership on employee performance both partially and simultaneously at PT. Success Mitra Sejahtera Kediri. This study used a quantitative approach with a causality method. The population in this study was all employees of PT. Success Mitra Sejahtera. The sample used in this study was 50 employees. The sampling technique uses proportional random sampling. The sample in this study is employees working at PT. Success of Mitra Sejahtera Kediri. The conclusion of this study is that recruitment has a significant effect on employee performance, competence does not have a significant effect on employee performance, and leadership has a significant effect on employee performance. Recruitment, competence, and leadership simultaneously affect employee performance at PT. Success of Mitra Sejahtera Kediri.